Academic Writing Analysis of Pesantren-Based University Students: Challenges, Practices,Preference, and Attitudes - Rofik, Abdur; Hidayah, Atinia; Christina; Sahid (Elite : English and Literature Journal, 2023)
Reflecting on teachers’ feedback and students’ responses, the study investigated students’ challenges in conducting academic writing, their preferences, and attitudes toward feedback, and teachers’ strategies to handle feedback on students’ written works. A case study was administrated. Three teachers and twenty-six undergraduate students were involved in the study. The findings demonstrated that the students were challenged in terms of grammar/surface structures, content, organization, vocabulary, and mechanism. Then, the teachers practiced various feedback i.e.; correction without comment, comment without correction, correction with comments, suggestion, and identification errors. Furthermore, in language use, the teachers’ preferences varied namely Indonesia/L1, English/EFL, and a combination between L1 and EFL. Students preferred those various teachers’ feedback. Then, the students’ attitudes toward handling feedback varied depending on every teacher's feedback type. Furthermore, the study unveiled that students responded positively to their teachers’ feedback such as requesting a more thorough explanation from their teachers, reading earlier pertinent research to improve their writing, and requiring some reflection time in response to their teachers' revisions.